(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Object-oriented analysis and design (OOA&D) tools support object analysis and design technologies and commonly use Unified Modeling Language (UML) notation with a variety of methodologies to assist in the creation of highly modular and reusable software. In this Paper, a brief overview of modeling of an application Real Time Scheduler using UML notations and their strategies with various problems has been discussed.